2004
DOI: 10.1093/nar/gkh878
|View full text |Cite
|
Sign up to set email alerts
|

A high resolution protein interaction map of the yeast Mediator complex

Abstract: Mediator is a large, modular protein complex remotely conserved from yeast to man that conveys regulatory signals from DNA-binding transcription factors to RNA polymerase II. In Saccharomyces cerevisiae, Mediator is thought to be composed of 24 subunits organized in four sub-complexes, termed the head, middle, tail and Cdk8 (Srb8-11) modules. In this work, we have used screening and pair-wise two-hybrid approaches to investigate protein-protein contacts between budding yeast Mediator subunits. The derived inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
238
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(266 citation statements)
references
References 51 publications
26
238
1
1
Order By: Relevance
“…4). Yeast two-hybrid screens support the interaction of Med17 with Med8C and -22 as well as Med6 (Guglielmi et al, 2004). That study also identified interactions between Med22 and -11 as well as Med16 and -5.…”
Section: Structural Conservation Of Mediator Submodules In Plantssupporting
confidence: 57%
See 3 more Smart Citations
“…4). Yeast two-hybrid screens support the interaction of Med17 with Med8C and -22 as well as Med6 (Guglielmi et al, 2004). That study also identified interactions between Med22 and -11 as well as Med16 and -5.…”
Section: Structural Conservation Of Mediator Submodules In Plantssupporting
confidence: 57%
“…The yeast Med14N (amino acid residues 1-259) connects the tail to the middle module through Med10 (Guglielmi et al, 2004); moreover, in Arabidopsis, Med14N (amino acids 1-959) interacts with a transcription regulator (Gonzalez et al, 2007). The yeast and Arabidopsis Med14 sequences aligned only for 171 amino acids in the N-terminal region, showing only 21% identity and 41% similarity (data not shown).…”
Section: Structural Conservation Of Mediator Submodules In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mediator complex was first identified in yeast, in which the detailed proteinprotein interaction network of the Mediator subunits was established (Guglielmi et al, 2004). The Mediator complex is conserved in eukaryotes and some subunits are conserved across species, with some specific subunits in certain species.…”
Section: Discussionmentioning
confidence: 99%